Perempuan dalam Partisipasi Politik di Indonesia - Anifatul Kiftiyah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
In social life, women are often seen as second-class humans. This is caused by patriarchal culture that considers men are in hingher position than women. Islam itself wants equality between men and women, for example in political field. There are two verses in Al-Qur’an that instruct muslims to conduct deliberations, ie. (QS Al-Syura: 38 and QS Ali ‘Imran: 159). In 1998, Indonesian women began to have courage to express their opinions marked by the emergence of movements that speak of equality between men’s and women’s positions, particularly in political field such as the representation of women in goverment. Indonesia has accomodated the role of women in politics, as instructed in constitution law No. 2 of 2008 and constitution law No. 7 of 2017. However in reality it is inversely proportional, the women involvement in political field, especially as legislators, has not been carried out optimally. This research will discuss the role of women in building national politics by using historical analysis method, which is in analyzing the data based on the history that has happened.